Concurrent bloat and rectal prolapse in a cow - Abdullah, Faez Firdaus Jesse; Adamu, Lawan; Saad, Mohd Zamri; Osman, Abdinasir Yusuf; Haron, Abdul Wahid; Awang, Dayang Norhaizam; Roslim, Noorashimah (SAGEYA Publishing, 2014)
Bloat commonly occurs during raining season in Malaysia as the legumes plants grow well during this season. A 4-year-old Friesian Holstein cow weighing 400 kg was presented to the Ambulatory Unit of the University Veterinary Hospital, Universiti Putra Malaysia with primary bloat and concurrent rectal prolapse, most probably a sequel to the bloat. Several means were attempted to treat the cow but were not feasible. Moreover, attempt to reposition the anus back were initiated yet the outcome was not very successful, partly due to the huge mass and the bloat was not able to be resolved after the administration of a debloating agent ( the “D-bloat”) as well as 3 liters of common cooking oil to resolve the bloating problem. Nevertheless, the treatments were not successful and in the end the owner decided to cull the cow.